Sp‐Carbon Incorporated Conductive Metal‐Organic Framework as Photocathode for Photoelectrochemical Hydrogen Generation. Issue 39 (24th August 2022) - Lu, Yang; Zhong, Haixia; Li, Jian; Dominic, Anna Maria; Hu, Yiming; Gao, Zhen; Jiao, Yalong; Wu, Mingjian; Qi, Haoyuan; Huang, Chuanhui; Wayment, Lacey J.; Kaiser, Ute; et al.
Abstract: Metal‐organic frameworks (MOFs) have attracted increasing interest for broad applications in catalysis and gas separation due to their high porosity. However, the insulating feature and the limited active sites hindered MOFs as photocathode active materials for application in photoelectrocatalytic hydrogen generation. Herein, we develop a layered conductive two‐dimensional conjugated MOF (2D c‐MOF) comprising sp‐carbon active sites based on arylene‐ethynylene macrocycle ligand via CuO4 linking, named as Cu3 HHAE2 . This sp‐carbon 2D c‐MOF displays apparent semiconducting behavior and broad light absorption till the near‐infrared band (1600 nm). Due to the abundant acetylene units, the Cu3 HHAE2 could act as the first case of MOF photocathode for photoelectrochemical (PEC) hydrogen generation and presents a record hydrogen‐evolution photocurrent density of ≈260 μA cm −2 at 0 V vs. reversible hydrogen electrode among the structurally‐defined cocatalyst‐free organic photocathodes. Abstract : The first sp‐carbon incorporated 2D c‐MOF (Cu3 HHAE2 ) single crystals are achieved based on the hexahydroxyarylene‐ethynyl macrocycle ligand. Owing to the abundant acetylene units, Cu3 HHAE2 acts as the first example of a MOF photocathode for highly efficient photoelectrochemical (PEC) hydrogen generation.